Media Pembelajaran Berbasis Augmented Reality (AR) dalam Pembelajaran Matematika di Sekolah Menengah Pertama - Subagiyo, Andri; Astutik, Widji; Wahyuni, Elien Dwi; Widhiati, Kesi; Maulidin, Mohammad Erfan; Listiani, Welas; Supriadi, Manan (Peneliti.net, 2023)
The aim of this research is to describe the implementation of AR-based learning media in Mathematics learning. This rearch is qualitative research using observation, documentation and questionnaire instruments. Implementation of AR learning media means students have HOTS skills. Students are more enthusiastic in learning Mathematics. The implementation of AR has a positive impact on students